Online and Hybrid Teaching and Learning: Enhance Effective Student Engagement and Experience - Kelum A. A. Gamage; Achini Gamage; Shyama C. P. Dehideniya (MDPI AG, 2022)
The COVID-19 pandemic has had an unprecedented impact on the global higher education system, where many universities have adapted to online and hybrid teaching and learning. They continue with some activities on campus, particularly laboratory-based teaching, but some content is delivered remotely. Significant adjustment to traditional face-to-face student engagement activities is crucial for the success of online and hybrid teaching and learning. This paper investigates the student engagement and experience in these environments. Engaged students are more likely to reach their full potential academically, and this paper identifies the areas for enhancement to student engagement activities. A survey was conducted (in Sri Lanka) to identify students' perceptions of engaging in activities during online and hybrid delivery. The results of the study illustrate a significant student engagement in learning whereas a pessimistic perception towards the transition to a completely online setting.